ANALISIS KELAYAKAN USAHA PADA PEMBENIHAN IKAN LALONGGOLOSUA NILA FARM SEBAGAI UPAYA PENGUATAN PERIKANAN BERKELANJUTAN DI KABUPATEN KOLAKA - Hasbiadi, Hasbiadi Hasbiadi; Purbaningsih, Yuli; Masitah, Masitah; Prihantini, Campina Illa; Rahim, Rahim (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
The potential of Indonesian fisheries cultivation is very promising with an economic value of USD 250 billion per year. One of the fishery commodities that is in demand by both domestic and foreign markets is tilapia. Tilapia is in demand by the community with increasing production and demand trends. Market opportunities are increasingly open, triggering the growth of tilapia fish businesses to develop both breeding, rearing and marketing. The purpose of the study is to analyze the business prospects of the Lalonggolosua Nila Farm fish seed business and to analyze the feasibility of the Lalonggolosua Nila Farm fish seed business in Kolaka Regency. The methods and approaches used are survey research and case studies. To answer the first objective related to business prospects, the IFAS Matrix and the IFAS Matrix Matrix are used. While the second problem related to business feasibility, income analysis, B/C ratio and R/C ratio are used. Research Results: The potential of Lalonggosua Nila Farm is a production of 120,000 per year, increasing to 600,000 per year if an investment is made to add 10 ponds. The projected profit per head is IDR 50-100. The potential for tilapia fish farming reaches 50 ha, especially in Lalonggolosua Village and the potential for marketing tilapia. Lalonggosua Tilapia Farm's income per year reaches Rp. 29,089,500 and this business is feasible with a business feasibility value of B/C ratio 1.167 and R/C ratio 2.167.